The three death sentences of Clarence Henderson: a battle for racial justice at the dawn of the Civil Rights Era : [july 25,1950] - Joyner, Chris (Abrams Press, 2022)
Preface -- Murder and chaos -- Carrollton -- A desperate manhunt -- "A very dark Negro" -- The first trial -- "Let me go home" -- Subversive elements -- The commies come to town -- "His fight is our fight" -- The NAACP takes charge -- A new trial ordered -- Dan Duke -- The second trial -- Ballistics, Nan, and a verdict -- New evidence, new trial -- The third trial -- Cornett v. Jones -- God and the NAACP.